Participação social na gestão de espaços públicos e atividade turística: análise de projetos de ocupação no Centro Histórico de São Luís - MA - JESUS, Vanderley Rabelo de (2020)
Social participation has acquired considerable attributions regarding the demands for urban management systems that adopt a decentralized conduct in the creation of public policies directed to the city's public spaces. When it comes to the implementation of tourism activity in these public spaces, the theme gains new developments, due to the tendency of tourism to change the city, both in the territorial context and at the social level. Based on this problem, it was investigated the existence of social participation in the planning and management of leisure and tourism projects carried out in public spaces in the Historic Center of São Luís do Maranhão. The research cut out the urban public spaces that are used for the operation of leisure and tourism projects promoted by the Public Power, namely, the Casa do Tambor de Crioula, the Largo/Palácio dos Leões and the Complexo Deodoro, where the projects Quarta do Tambor, Pôr do Sol in the Palácio and the Sarau Histórico, respectively, take place. To this end, bibliographic and documentary resources were used to compose a theoretical framework on the themes pertinent to the study. Subsequently, through semi-structured interviews with local residents present during the projects and with managers of the staff of the State Secretariat of Culture and the Municipal Secretariat of Tourism, where was verified the presence of mechanisms for the insertion of social participation in their planning and management stages, contemplating the phases of design, implementation and evaluation of projects. Finally, a qualitative analysis was made, based on the results of the data obtained, to understand the dimensions of social participation in these leisure and tourism projects that occupy the public spaces of the Historic Center of São Luís. The results point to a fragility in the mechanisms of democratization of the management of these policies of occupation of public spaces, since, participating only as spectators of the projects, the local residents have their limited and insufficient performance to make their participation effective. Therefore, it is stated the need for decentralization of the management of leisure and tourism projects, as well as other policies that will occupy the public spaces of the Historic Center of São Luís, so that, by means of good participatory methods, the democratization of city management instruments occurs.